Outcome Related to Level of Targeted Temperature Management in Postcardiac Arrest Syndrome of Low, Moderate, and High Severities: A Nationwide Multicenter Prospective Registry. Issue 8 (August 2021) - Nishikimi, Mitsuaki; Ogura, Takayuki; Nishida, Kazuki; Hayashida, Kei; Emoto, Ryo; Matsui, Shigeyuki; Matsuda, Naoyuki; Iwami, Taku
Abstract : OBJECTIVES: The optimal target temperature during targeted temperature management for patients after cardiac arrest remains under debate. The aim of this study was to evaluate the association between targeted temperature management at lower target temperatures and the neurologic outcomes among patients classified by the severity of postcardiac arrest syndrome. DESIGN: A multicenter observational study from the out-of-hospital cardiac arrest registry of the Japanese Association for Acute Medicine, which is a nationwide prospective registry of out-of-hospital cardiac arrest patients. SETTING: A total of 125 critical care medical centers or hospitals with an emergency care department across Japan. PATIENTS: A total of 1, 111 out-of-hospital cardiac arrest patients who had received targeted temperature management. MEASUREMENTS AND MAIN RESULTS: We divided all 1, 111 postcardiac arrest syndrome patients treated with targeted temperature management into two groups: those who received targeted temperature management at a lower target temperature (33–34°C) and those who received targeted temperature management at a higher target temperature (35–36°C). In regard to classification of the patients, we divided the patients into three categories of severity (low, moderate, and high severities) using the risk classification tool, post-Cardiac Arrest Syndrome for Therapeutic hypothermia, which was previously validated. The primary outcome was the percentage of patients with a good neurologic outcome at 30 days, and the secondary outcome was the survival rate at 30 days. Multivariate analysis showed that targeted temperature management at 33–34°C was significantly associated with a good neurologic outcome and survival at 30 days in the moderate severity (odds ratio, 1.70 [95% CI, 1.03–2.83] and 1.90 [95% CI, 1.15–3.16], respectively), but not in the patients of low or high severity (pinteraction = 0.033). Propensity score analysis also showed that targeted temperature management at 33–34°C was associated with a good neurologic outcome in the moderate-severity group ( p = 0.022). CONCLUSIONS: Targeted temperature management at 33–34°C was associated with a significantly higher rate of a good neurologic outcome in the moderate-severity postcardiac arrest syndrome group, but not in the low- or high-severity group. Abstract : Supplemental Digital Content is available in the text.